New dynamical observer for a batch crystallization process based on solute concentration. (March 2020) - Brivadis, Lucas; Andrieu, Vincent; Chabanon, Élodie; Gagnière, Émilie; Lebaz, Noureddine; Serres, Ulysse
Highlights: A new observer is introduced to estimate the Crystal Size Distribution (CSD). The observer follows the Kazantzis-Kravaris/Luenberger methodology. Only the solute concentration, temperature and a growth rate model are needed. A theoretical observability analysis of the system is investigated. The performances of the introduced observer are tested and analyzed numerically. Abstract: In this paper a new observer is introduced to estimate the Crystal Size Distribution (CSD) only from the measurements of the solute concentration, temperature and a model of the growth rate. No model of the nucleation rate is needed. This approach is based on the use of a Kazantzis-Kravaris/Luenberger observer which exponentially estimates functionals of the CSD. Then, the full state is estimated by means of a Tikhonov regularization procedure. Numerical simulations are provided. Our approach relies on an infinite-dimensional observer, contrarily to the usual moment based observers.